2019
DOI: 10.1002/hbm.24578
|View full text |Cite
|
Sign up to set email alerts
|

Functional and effective reorganization of the aging brain during unimanual and bimanual hand movements

Abstract: Motor performance decline observed during aging is linked to changes in brain structure and function, however, the precise neural reorganization associated with these changes remains largely unknown. We investigated the neurophysiological correlates of this reorganization by quantifying functional and effective brain network connectivity in elderly individuals (n = 11; mean age = 67.5 years), compared to young adults (n = 12; mean age = 23.7 years), while they performed visually‐guided unimanual and bimanual h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 78 publications
3
22
1
Order By: Relevance
“…Finally, we found that AEC measures exhibited an age-related increase in connectivity within all frequency bands across all brain networks, apart from the visual network which showed a decrease in connectivity within the high alpha and high beta frequency bands. These results align well with a recent study where Larivière et al reported lower beta-band connectivity in the visual network and higher beta-band connectivity in all other brain networks with age (Larivière et al, 2019). Higher functional connectivity in older adults has been associated with a lower cognitive reserve (López et al, 2014), and individuals with mild cognitive impairment exhibit an enhancement of the strength of functional connections (Bajo et al, 2010;Buldú et al, 2011).…”
Section: Cca Loadingssupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, we found that AEC measures exhibited an age-related increase in connectivity within all frequency bands across all brain networks, apart from the visual network which showed a decrease in connectivity within the high alpha and high beta frequency bands. These results align well with a recent study where Larivière et al reported lower beta-band connectivity in the visual network and higher beta-band connectivity in all other brain networks with age (Larivière et al, 2019). Higher functional connectivity in older adults has been associated with a lower cognitive reserve (López et al, 2014), and individuals with mild cognitive impairment exhibit an enhancement of the strength of functional connections (Bajo et al, 2010;Buldú et al, 2011).…”
Section: Cca Loadingssupporting
confidence: 92%
“…It is widely used to decompose multivariate datasets into a set of successive orthogonal components that explain the maximum amount of the data variance (e.g. Amico and Goñi, 2017;Larivière et al, 2019). The obtained principal components correspond to the maximal modes of variation and hence correspond to the most prominently changing features in the dataset.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
“…In summary, the older adults showed significant deterioration in grip force control and greater hemodynamic activity during both the FTTs than did the young adults, suggesting a greater computational effort and oxygen supply during the motor tasks (Ward, 2006) which represent a general age-related compensatory mechanism of changes in the sensorimotor network (Noble et al, 2011;Larivière et al, 2019). In contrast, increases in left PMC beta activity that are related to deteriorations in grip force regulation in older adults are task-complexity-dependent, thus representing an increased cognitive effort during motor planning or a compensatory mechanism of deficits in processing the sensory feedback within the sensorimotor network.…”
Section: Discussionmentioning
confidence: 98%
“…Abbreviations: PMC, premotor cortex; SMC, sensorimotor cortex; r = Pearson correlation coefficient; Significance level p < 0.05 * . Noble et al, 2011;Larivière et al, 2019). Nevertheless, the results of deteriorations in grip force control and higher hemodynamic brain activity in older subjects cannot only be associated with the grip force tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation